Filosofía del derecho penal en el sistema democrático Mexicano - Fernández Reyes, Pamela Lili (2017)
It is necessary to determine and establish the purpose of Criminal Law as it is essential to clarify its field of action in the dialectic discussion of which are legal assets or ethical-social values that must be protected. The purpose of criminal law is both the protection of legal assets from potential threats or danger and ethical-social, axiological protection, including legal assets and general prevention confirming regulatory recognition.